Anointing In The Historical Books Of The Old Testament - Sarah Wassar (International Journal of Christian Education and Philosophical Inquiry, 2024)
When Jesus appeared to the disciples, he said: "Peace be with you; he breathed on them and said: Receive the Holy Spirit", John 20:21-22. Shortly after that Jesus ascended into heaven. The disciples prayed for ten days in Jerusalem and the Holy Spirit came down as promised by Jesus, (Acts 1:8). In addition, no one else, be it prophets, apostles, church fathers or pastors may breathe and tell people to receive the Holy Spirit. This study aims to find the views and attitudes of Christianity in ordaining ministry or worship. In this study, the method used is qualitative descriptive with an approach to an understanding and comprehension of the importance of receiving the anointing of the Holy Spirit so as not to be extreme in the completion of ministry or worship. The Holy Spirit anoints someone so that the person experiences a change in life to become spiritually qualified and has the divine ability to carry out ministry according to his calling, with abilities that exceed human strength.